5G: Vision and Requirements for Mobile Communication System towards Year 2020. (6th April 2016) - Liu, Guangyi; Jiang, Dajie
Abstract : The forecast for future 10 years' traffic demand shows an increase in 1000 scales and more than 100 billion connections of Internet of Things, which imposes a big challenge for future mobile communication technology beyond year 2020. The mobile industry is struggling in the challenges of high capacity demand but low cost for future mobile network when it starts to enable a connected mobile world. 5G is targeted to shed light on these contradictory demands towards year 2020. This paper firstly forecasts the vision of mobile communication's application in the daily life of the society and then figures out the traffic trends and demands for next 10 years from the Mobile Broadband (MBB) service and Internet of Things (IoT) perspective, respectively. The requirements from the specific service and user demands are analyzed, and the specific requirements from typical usage scenarios are calculated by the defined performance indicators. To achieve the target of affordable 5G service, the requirements from network deployment and operation perspective are also captured. Finally, the capabilities and the efficiency requirements of the 5G system are demonstrated as a flower. To realize the vision of 5G, "information a finger away, everything in touch, " 5G will provide the fiber-like access data rate, "zero" latency user experience, and connecting to more than 100 billion devices and deliver a consistent experience across a variety of scenarios with the improved energy and cost efficiency by over a hundred of times.